Urinary levels of organophosphate flame retardants metabolites in a young population from Southern Taiwan and potential health effects - Chen, Feng-Shun; Chen, Chih-Cheng; Tsai, Ching-Chang; Lu, Jian-He; You, Huey-Ling; Chen, Ching-Mei; Huang, Wan-Ting; Tsai, Kai-Fan; Cheng, Fu-Jen; Kung, Chia-Te; Li, Shau-Hsuan; Wang, Chin-Chou; et al. (Frontiers in Endocrinology, 2023)
Background: Organophosphate flame retardants (OPFRs) are widely distributed in the environment and their metabolites are observed in urine, but little is known regarding OPFRs in a broad-spectrum young population from newborn to 18 years of age. Objectives: Investigate urinary levels of OPFRs and OPFR metabolites in Taiwanese infants, young children, schoolchildren, and adolescents from the general population. Methods: Different age groups of subjects (n=136) were recruited from southern Taiwan to detect 10 OPFR metabolites in urine. Associations between urinary OPFRs and their corresponding metabolites and potential health status are also examined. Results: The mean level of urinary Σ10 OPFR in this broad-spectrum young population is 2.25 μg/L (standard deviation (SD) of 1.91 μg/L). Σ10 OPFR metabolites in urine are 3.25±2.84, 3.06±2.21, 1.75±1.10, and 2.32±2.29 μg/L in the age groups of newborn, 1-5 yr, 6-10 yr, and 11-18 yr, respectively, and border-line significant differences were found in the different age groups (p=0.125). The OPFR metabolites of TCEP, BCEP, DPHP, TBEP, DBEP and BDCPP predominate in urine and comprise more than 90% of the total. TBEP was highly correlated with DBEP in this population (r=0.845, p<0.001). The estimated daily intakes (EDIs) of Σ5OPFRs (TDCPP, TCEP, TBEP, TNBP, and TPHP) are 2230, 461, 130, and 184 ng/kg bw/day for newborns, 1-5 yr children, 6-10 yr children, and 11-17 yr adolescents, respectively. The EDI of Σ5OPFRs for newborns is 4.83-17.2 times higher than the other age groups. Urinary OPFR metabolites are significantly correlated with birth length and chest circumference in newborns. Conclusions: To our knowledge, this is the first investigation of urinary OPFR metabolite levels in a broad-spectrum young population. There tended to be a higher exposure rates in both newborns and pre-schoolers, though little is known about their exposure levels or factors leading to exposure in the young population. Further study should clarify the exposure levels and factor relationships.